2013
DOI: 10.1007/s13197-013-1064-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modified atmosphere packaging on the shelf life of lal peda

Abstract: Lal peda is a traditional dairy-based sweet, popular in the Indian subcontinent, but it has a poor shelf life. The lal peda samples were packed in polyethylene bags filled with 3 different gaseous compositions (Air, 70 % N2: 30 % CO2 and 98 % N2) and stored at 10°C. The shelf life was evaluated on the basis of changes in the microbial status of the product such as total plate count, yeast and molds and coliform counts and also the physico-chemical changes such as hydroxy methyl furfural (HMF), thiobarbituric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 20 publications
17
27
0
Order By: Relevance
“…This decline in the adhesiveness could be due to the decrease in free moisture during the storage. Similar trend in adhesiveness was observed in the Lal peda samples by Jha et al (2013).…”
Section: Changes In Textural Characteristicssupporting
confidence: 84%
See 3 more Smart Citations
“…This decline in the adhesiveness could be due to the decrease in free moisture during the storage. Similar trend in adhesiveness was observed in the Lal peda samples by Jha et al (2013).…”
Section: Changes In Textural Characteristicssupporting
confidence: 84%
“…However, the springiness increased with further increase in storage period and varied significantly (P<0.05) with variation in the temperature and gas composition. Jha et al (2013) reported similar observations in Lal peda samples stored under MAP conditions. The springiness values in Kalakand were lower than those reported in Lal peda ), but higher than those reported in brown peda by Londhe et al (2012).…”
Section: Changes In Textural Characteristicssupporting
confidence: 73%
See 2 more Smart Citations
“…However, commercial application of modern packaging techniques for traditional dairy foods is still limited [6]. Reports have been published on the application of MAP for preservation of Peda [7], Paneer [8, 9], Malai peda [10], Brown peda [11] and Lal peda [6] which shows that this packaging technique holds a promise for enhancing the shelf life of traditional dairy foods.…”
Section: Introductionmentioning
confidence: 99%